2013
DOI: 10.1186/1756-9966-32-27
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of epigenetic modulators and differentiation inducers on human medulloblastoma cell lines

Abstract: BackgroundMedulloblastoma (MB) is the most common malignant brain tumor in childhood with a 5-year survival of approximately 60%. We have recently shown that treatment of human MB cells with 5-aza-2’-deoxycytidine (5-aza-dC) reduces the clonogenic survival significantly. Here, we tested combinatorial effects of 5-aza-dC with other epigenetic (valproic acid, SAHA) and differentiation-inducing drugs (resveratrol, abacavir, retinoic acid) on human MB cells in vitro to intensify the antitumor therapy further.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…We have already shown that resveratrol decreases the survival in the most common human medulloblastoma cell lines synergistically with irradiation (manuscript in preparation) and on its own (Patties, Kortmann, & Glasow, ). The resveratrol concentration of 15 μmol/L used in the present study led to a 30% reduction of metabolic activity in medulloblastoma cell lines (Patties et al., ). It should be feasible for a treatment in humans as it is still well below the concentration of 40 μmol/L, which is maximally achievable after intravenous injection (Asensi et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…We have already shown that resveratrol decreases the survival in the most common human medulloblastoma cell lines synergistically with irradiation (manuscript in preparation) and on its own (Patties, Kortmann, & Glasow, ). The resveratrol concentration of 15 μmol/L used in the present study led to a 30% reduction of metabolic activity in medulloblastoma cell lines (Patties et al., ). It should be feasible for a treatment in humans as it is still well below the concentration of 40 μmol/L, which is maximally achievable after intravenous injection (Asensi et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, resveratrol has been shown to synergize with paclitaxel (Jazirehi and Bonavida 2004), etoposide (Amiri et al 2013), gemcitabine (Harikumar et al 2010), bortezomib and thalidomide (Bhardwaj et al 2007) and histone deacetylase inhibitors (HDACi) (Yaseen et al 2012). With respect to childhood cancers, it has been demonstrated to cooperate with etoposide, doxorubicin, cytarabine, actinomycin D, methotrexate and paclitaxel (Fulda and Debatin 2004), TRAIL (Fulda and Debatin 2005) and immunotherapy (Soto et al 2011) in neuroblastoma, with decitabine in medulloblastoma (Patties et al 2013) and with vincristine in retinoblastoma (Mahida et al 2013). Only few combination studies have been conducted using synthetic STACs, but those that have done so have reported a synergistic effect of SRT1720 with cisplatin (Shin et al 2014) and bortezomib and dexamethasone (Chauhan et al 2011) and of SRT2183 with HDACi (Scuto et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Resveratrol-but none of the synthetic STACs-has been tested in other childhood cancers, e.g., in acute lymphoblastic leukemia (Dorrie et al 2001;Wieder et al 2001), in neuroblastoma Debatin 2004, 2005;Liontas and Yeger 2004;Nicolini et al 2001;Rigolio et al 2005;Soto et al 2011;van Ginkel et al 2007), in medulloblastoma (Patties et al 2013;Wang et al 2003) and in retinoblastoma (Mahida et al 2013), leading to the conclusion that it has potential as chemotherapeutic agent against pediatric malignancies. Here we show that resveratrol and SRT1720 were effective in ES as well.…”
Section: Discussionmentioning
confidence: 97%
“…This has provided the basis for not only a new molecular classification of medulloblastomas, but also the foundation for functional studies in animal models (33,34). An interesting outcome of these high throughput studies is the uncovering of somatic mutations, amplifications and loss of chromatin modifying enzymes, implicating epigenetic perturbations in medulloblastoma genesis (35).…”
Section: Discussionmentioning
confidence: 99%